(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
The present study analyzes the composition and distribution of gelatinous zooplankton in the Ecuadorian sea from July 2017 to April 2018. The coastal profile was divided into two zones, ZI included the province of Esmeraldas and the northern part of the province of Manabí; while, ZII was comprised from the southern part of the province of Manabí to the northern part of the province of Santa Elena. A total of 54 species were identified, where Doliolum gegenbauri, Doliolum nationalis, Abylopsis tetragona, Cyclosalpa pinnata, Aglaura hemistoma and Ropalomena velatum were the most representative. Other groups with little representation were Copelata, Leptothecata, Narcomedusae, Anthoathecata, Coronatae, Semaeostomeae and Beroida. In regard of the spatial distribution, ZII showed the highest density; however, no significant differences were found between both areas (p = 0.3316). ZI and ZII presented a specific richness of 48 species, although exclusive species were found for each zone. Due to species frequency and distribution, they are considered to be characteristic of the Ecuadorian sea. Furthermore, the orders Doliolida and Siphonophorae are the most important within gelatinous zooplankton because of their number of species and density. Species density showed a low correlation with temperature and salinity, which indicates that gelatinous zooplankton populations might be influenced by biotic variables.